Detection And Genetic Characterization Of Major Pathogens Isolated From Bovine Mastitis In Rajasthan - Gupta, Neena; Faridi, Farah; Maherchandani, S.; Kashyap, S.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The present study was contemplated with an aim to detect and evaluate the major pathogens associated with clinical mastitis in bovines. The milk samples were obtained from the cows suffering from mastitis from different areas of Bikaner and veterinary clinical complex RAJUVAS, Rajasthan. After subjecting the samples to microbiological detection protocols, their 16S–23S rRNA gene internal transcribed spacer (ITS) regions were characterized and the feasibility of using ITS sequences to discriminate between five bacterial species was validated. The conventional bacteriological and PCR based examinations showed incidence of 20 (40%) isolates of E. coli, 16 (32%) isolates of S. aureus, 8 (16%) isolates of P. aeruginosa, and 1 (2%) isolate of Streptococcus spp. The sensitivity and specificity of the test was evaluated using standard cultures.PCR was found to be more sensitive than conventional culture methods for detection of common mastitic pathogens. The results suggest that the PCR assay could be used as an alternative method in routine diagnosis for rapid, sensitive and specific simultaneous detection of S. aureus, S. agalactiae, S. dysgalactiae, S. uberis, E. coli and P. aeruginosa in milk samples.
Keywords: Bovine; Culture; E. Coli; Milk; PCR; Subclinical Mastitis